A Study on Pain and Hemodynamic Parameters in Minor Gynecological Procedures: Propofol – Fentanyl Vs. Ketamine – Midazolam
Background: One of the minor obstitrical procedures is dilation and curettage; pain usually occurs during it. Consequently, an anesthetic drug desires sufficient analgesia, brisk onset, and recovery. Objective: To evaluate two groups of drug combinations midazolam 0.08mg/kg – ketamine (0.5mg/kg) and propofol with (1mg/kg) –fentanyl dose (1mcg /kg)